Microstructure of veneered zirconia after surface treatments: A TEM study - Grigore, Alexandra; Spallek, Stefanie; Petschelt, Anselm; Butz, Benjamin; Spiecker, Erdmann; Lohbauer, Ulrich (Dental Materials, 2013)
Signcance. Regardless of the treatment protocol and produced roughness, the veneering ceramic perfectly sealed the zirconia surface. XRD showed an increased amount of monoclinic phase on the surface treated zirconia. However after thermal treatment, the monoclinic phase was re-transformed into the tetragonal polymorph. TEM/SAED analysis has found indication for a greater extend of the monoclinic transformation into the bulk zirconia compared to the treatment related defective zone depth. (C) 2013 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Y-TZP; X-ray diffraction; Martensitic transformation; Sandblasting; Bur drilling; Annealing